2022
DOI: 10.1021/acsaelm.1c01248
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Self-Powered Panchromatic Organic Photodiode and Its Application in Biomedical Devices

Abstract: Non-fullerene acceptor (NFA)-based optoelectronic devices have received great research interest because of their unique optoelectronic characteristics like tunable bandgap, strong near-infrared (NIR) light absorption, and enhanced stability. However, the demonstration of a self-powered NIR broadband photodiode with excellent photoresponse and low dark current density comparable to that of commercial inorganic counterpart remains a challenge. Herein, the high-performance solution-processed self-powered organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Notably, these values are similar to those of the recently reported OPDs (Table S4). However, the R and D * of the flexible OPDs fabricated with the ZnO-NP and ZnO-NP:KBr ETLs/HBLs were gradually decreased after bending 500 and 1000 times at r = 4.0 mm, whereas the ZnO-NP:DFPBr-6 device produced almost identical R and D * regardless of bending cycles (Figure d). The R values of the ZnO-NP and ZnO-NP:KBr devices were decreased to 0.06 and 0.02 A/W corresponding to 85 and 95% reductions, respectively, after bending 1000 times at r = 4.0 mm (Table S3).…”
Section: Resultsmentioning
confidence: 97%
“…Notably, these values are similar to those of the recently reported OPDs (Table S4). However, the R and D * of the flexible OPDs fabricated with the ZnO-NP and ZnO-NP:KBr ETLs/HBLs were gradually decreased after bending 500 and 1000 times at r = 4.0 mm, whereas the ZnO-NP:DFPBr-6 device produced almost identical R and D * regardless of bending cycles (Figure d). The R values of the ZnO-NP and ZnO-NP:KBr devices were decreased to 0.06 and 0.02 A/W corresponding to 85 and 95% reductions, respectively, after bending 1000 times at r = 4.0 mm (Table S3).…”
Section: Resultsmentioning
confidence: 97%
“…V OC versus P light was plotted as shown in Figure 2e. The degree of trap-assisted recombination can be evaluated by n value as shown in the following Equation (3), where K B is the Boltzmann constant, and T is the absolute temperature. The nK B T/q value is related to degree of trap-assisted recombination, and closer to 1 indicates smaller trapassisted recombination.…”
Section: Opd Propertiesmentioning
confidence: 99%
“…Organic photodetectors (OPDs) have been rapidly developed for decades due to light weight, low production cost, flexibility, controllable energy band gap, low voltage operation, and solution-processibility. [1][2][3][4][5][6] Thus, OPDs are regarded to be one of the most promising printable devices for the portable and wearable optical communication system and image sensors. [7][8][9] As light-absorbing materials, numerous types of materials have been developed and the most successful materials are conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…59 Joseph et al reported that panchromatic LED can be utilized as a light source for heart rate sensing. 60 Hence, it would be extremely valuable in enabling organic LEDs with all colors as well as medical application viability if a single nanoparticle can be made of nonprecious metals and meanwhile extend the enhancement to the red or even NIR region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lee reported that panchromatic LED display screen not only has the characteristics of high contrast but also is soft in displayed color and has an effect closer to the visual high-definition effect . Joseph et al reported that panchromatic LED can be utilized as a light source for heart rate sensing . Hence, it would be extremely valuable in enabling organic LEDs with all colors as well as medical application viability if a single nanoparticle can be made of nonprecious metals and meanwhile extend the enhancement to the red or even NIR region.…”
Section: Introductionmentioning
confidence: 99%